(untitled) (Journal of Scientific Research, 2018)
Antibiofilm phenomenon has become a novel area of research for removing deleterious biofilm. In the present study, strains from different environmental sources were tested for screening antibiofilm compounds. Crude extracts from various microorganisms were evaluated for antibiofilm phenomenon through crystal violet assay and growth curve analysis. Characterization of antibiofilm compound was performed by pre-coating microtiter plate and Cell Surface Hydrophobicity experiment. Among the organisms, cell free extracts (5% v/v) from Bacillus subtilis S01 inhibited the development of E. coli PHL628 biofilm by 63%. The cell free extracts possessed no amylase activity and had no effect on the planktonic growth of biofilm forming bacteria. Moreover, no competition with quorum sensing analogues was found with the extract. Biofilm formation was more inhibited (76%) in the B. subtilis S01 extract pre-coated wells than uncoated wells (62%). However, no effect on preformed biofilm was observed with the extracts of B. subtilis S01. The extract also reduced the cell surface hydrophobicity (69%) of the biofilm forming bacteria. The present study indicated that the crude extracts of B. subtilis S01 from soil origin has anti-adherence properties towards biotic and abiotic surfaces and thus can be a potential candidate in preventing the development of biofilm.